Italian conventions in Gomes’ orchestral writing: A transnational possibility - Kerr, Isaac William (Seven Editora, 2024)
The mastery of Carlos Gomes over the Italian musical tradition can be elucidated by the success of his opera Salvator Rosa (1874), which, according to the author, was crafted in accordance with Italian taste. The Brazilian composer’s journey in the realm of opera, marked by both triumphs and setbacks, is extensively documented in his biographies, yet remains relatively unexplored in investigations focusing on his music within a transnational context. This study seeks to present some procedures employed in Gomes’s orchestral writing through the teachings of three widely accepted treatises in the teaching of musical composition in Italy, more specifically in Milan. They are: Il Maestro di composizione by Bonifazio Asioli, Corso di composizione musicale by Anton Reicha (translated by L. Rossi), and Grande trattato di strumentazione ed orchestrazione moderne by Hector Berlioz (translated by A. Mazzucato). DOI:https://doi.org/10.56238/sevened2023.008-021